Energy balance of adolescent elite athletes during intensive training - Ismail, M. N.; Poo, K. H. (2000)
Adequate energy intake to match high-energy requirement is an essential component in sports performance. Energy needs of 21 adolescent athletes (8 rhythmic gymnasts and 13 divers, aged between 13 - 16 years) residing in Bukit Jalil Sports School, in preparation of the 1998 Commonwealth Games were studied. The parameters assessed included anthropometric measurements, a 3-day weighed food intake and daily physical activity patterns carried out simultaneously with the food intake study. The basal metabolic rates (BMR) of athletes were measured by an indirect calorimetry technique under standardized conditions using a Deltatrac unit. The mean body weight and height were 39.0 ± 4.3 kg, 1.58 ± 0.07 m for rhythmic gymnasts, 42.4 ± 7.6 kg, 1.48 ± 0.08 m for female divers and 34.2 ± 6.6 kg, 1.41 ± 0.01 m for male divers. Mean daily energy intake for gymnasts were 1540 ± 247 kcal, 1510 ± 271 kcal for female divers and 2040 ± 518 kcal for male divers while mean energy expenditure were 2187 ± 240 kcal for gymnasts, 2207 ± 391 kcal for female divers and 1817 ± 353 kcal for male divers. The energy balance for gymnasts were -647 kcal, -697 kcal for female divers and 223 kcal for male divers. The mean daily activity pattern for gymnasts revealed that 62% of the day was spend in light activity, 13% moderate activity and 25% of the day in training, while the divers spent 63% of the day in light activity, 8% moderate activity and 29% in training. The mean BMR for female athletes was 1182 ± 118 kcal and 1200 ± 200 kcal for male athletes. The measured BMR was in close agreement with Henry and Rees' (1991) predicted equations however, the mean measured BMR for the female athletes was statistically different with the BMR predicted from the FAO/WHO/UNU (1985) equations. The mean physical activity level (PAL) of female gymnasts and divers were 1.86 and 1.51 for male divers. The proposed energy requirement for gymnasts is 56 kcal/kg body weight, 53 kcal/kg body weight for male divers and 52 kcal/kg body weight for female divers. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)